2017
DOI: 10.1186/s41021-017-0074-z
|View full text |Cite|
|
Sign up to set email alerts
|

New insight for metformin against bladder cancer

Abstract: International Agency for Research on Cancer (IARC) estimated that bladder cancer is the ninth most common cancer in the world, with 430,000 new cases and 165,000 deaths in 2012. Bladder cancer represents the fourth most common cancer in men and ninth most common cancer in women. It is the second most prevalent cancer in men 60 years of age or older in United States. Looking further down, continuing advancements in cancer research could potentially offer more choices for clinician and patient with longer surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 88 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…There have been many reports of the versatile nature of metformin in the inhibition of cancer. 28 30 Our previous study confirmed the effects of metformin in the suppression of HIF-1α expression and the subsequent enhancement of the therapeutic effects of cisplatin. 23 In addition, metformin is a clinically approved drug which may have great potential for future clinical trials if the capacity to re-sensitize tumors to gefitinib is shown.…”
Section: Resultssupporting
confidence: 73%
“…There have been many reports of the versatile nature of metformin in the inhibition of cancer. 28 30 Our previous study confirmed the effects of metformin in the suppression of HIF-1α expression and the subsequent enhancement of the therapeutic effects of cisplatin. 23 In addition, metformin is a clinically approved drug which may have great potential for future clinical trials if the capacity to re-sensitize tumors to gefitinib is shown.…”
Section: Resultssupporting
confidence: 73%
“…The comorbidities related to the risk of bladder cancer considered in this study were diabetes mellitus (DM) (ICD-9-CM code 250), [ 17 ] hypertension (ICD-9-CM codes 401–405), [ 18 ] obesity (body mass index > 27) (ICD-9-CM codes 278 and 278.0), [ 19 ] chronic obstructive pulmonary disease (COPD) (as a proxy of smoking; ICD-9-CM codes 490–496), [ 20 ] and uremia (ICD-9-CM code 586). [ 21 ] Medications related to the risk of bladder cancer were aspirin (ATC codes B01AC06 and N02BA01), [ 22 ] nonsteroidal anti-inflammatory drugs (NSAIDs) (ATC code M01A), [ 23 ] metformin (ATC code A10BA02), [ 24 ] rosiglitazone (ATC code A10BG02), [ 25 ] and pioglitazone (ATC codeA10BG03). [ 25 ]…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that HER2 expression has been reported in various pediatric cancers including Wilm's tumor; however, in comparison with adult cancers, several features of HER2 such as expression pattern and clinical outcome perhaps are different in pediatric cancers [171]. Fascinatingly, there are many similarities in the risk factors of pancreatic and urinary bladder cancers such as tobacco use and obesity-related conditions like diabetes and metabolic syndrome [172], [173], [174], [175], [176].…”
Section: Tumors Of the Genitourinary/excretory Organsmentioning
confidence: 99%